New and interesting species of the genus Bryaxis Kugelann, 1794 (Coleoptera, Staphylinidae, Pselaphinae) from Croatia - Bekchiev, Rostislav; Hlaváč, Peter (Zootaxa, 2016)
New data on the genus Bryaxis Kugelann, 1974 from Croatia are presented. Two new species, Bryaxis bedeki sp. nov. and Bryaxis biokovensis sp. nov. are described and illustrated. Bryaxis issensis (J. Müller, 1909) is redescribed based on six males collected at the type locality, in the cave Špilja kod Vlore on the island of Vis, and the aedeagus of this species is figured for the first time. New distributional data of Bryaxis scapularis (Reitter, 1881), Bryaxis crepsensis crepsensis (J. Müller, 1947), Bryaxis stolzi (Machulka, 1932), and Bryaxis erichsonii erichsonii (Kiesenwetter, 1849) are also provided.